SadB is a Pseudomonas aeruginosa global regulator - Papangeli, Maria (2022)
Bacteria can adhere to almost any surface and form resistant biofilm communities. These pose a major clinical burden as they can form on medical devices such as catheters and are hard to prevent. Catheter- associated urinary tract infections (CAUTIs) are the most common nosocomial infection as they represent ~40% of all nosocomial infections.